Adsorption of ammonium ion using zeolite, chitosan, bleached fibre and activated carbon - N N Safie; Abu Zahrim Yaser; Mariani Rajin; Noor Maizura Ismail; Sariah Saalah; S M Anisuzzaman; A D Rahayu; H Huslyzam; R Jennisha; T T H Calvin (IOP Publishing, 2019)
Several materials have been studied for the adsorption of ammonium ion from synthetic solution. Zeolite is having the highest adsorption capacity (3.160 mg/g) with fast reaction time followed by chitosan (2.5770 mg/g). Activated carbon derived from Tarap (Artocarpus odoratissimus) and rice husk shows better performance than the low-cost bleached fibres